2020
DOI: 10.7150/thno.45843
|View full text |Cite
|
Sign up to set email alerts
|

JP1 suppresses proliferation and metastasis of melanoma through MEK1/2 mediated NEDD4L-SP1-Integrin αvβ3 signaling

Abstract: Background: JWA gene is known to down-regulate SP1 and reduces the expression level of Integrin αvβ3. Here, we identified a functional polypeptide (JP1) based on the active fragment of the JWA protein to suppress melanoma growth and metastasis by inhibiting the Integrin αvβ3. Methods: We conducted a series of melanoma growth and metastasis mouse models to evaluate anti-melanoma effect of JP1 peptide. 18 F-labeled JP1 ( 18 F-NFP-JP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…CXCl12/CXCR4 can directly activate the integrin αvβ3 signaling pathway and then promote cell migration [ 45 ]. Activation of integrin αvβ3 is associated with invasion and metastasis of multiple tumors [ 46 ]. However, the recruitment of MSCs in the bone defect microenvironment has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…CXCl12/CXCR4 can directly activate the integrin αvβ3 signaling pathway and then promote cell migration [ 45 ]. Activation of integrin αvβ3 is associated with invasion and metastasis of multiple tumors [ 46 ]. However, the recruitment of MSCs in the bone defect microenvironment has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Our conclusion is supported by the following lines of evidence: (1) NEDD4L binds to UBE2T under the physiological conditions; (2) Cellular levels of UBE2T can be decreased or increased by NEDD4L overexpression or depletion, respectively; (3) The half-life of UBE2T protein is shortened or extended by NEDD4L overexpression or depletion, respectively; (4) NEDD4L leads to UBE2T ubiquitylation. NEDD4L has been shown bind to and ubiquitylate many cellular proteins for targeted degradation [ 35 , 36 ], but has never about it targets UBE2T. Taken together, we first report that UBE2T is a novel physiological substrate of the E3 ubiquitin ligase NEDD4L.…”
Section: Discussionmentioning
confidence: 68%
“…Emerging evidences have reported that NEDD4L may function as a tumor suppressor that is frequently reduced in human carcinomas of pancreatic [ 37 ], colorectal [ 35 ], melanoma [ 36 ], ovarian [ 38 ] and lung [ 25 , 26 ]. But some studies reported that NEDD4L promoted lung cancer cell survival [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neural precursor cell expresses developmentally downregulated 4-like (NEDD4L), a member of the NEDD4 family that contains a HECT domain for Ub protein ligation [ 23 ]. NEDD4L has been reported to be downregulated in multiple types of cancers and acts as a tumour suppressor gene in melanoma [ 24 ], colorectal cancer [ 25 ], lung cancer [ 26 ], and other cancers.…”
Section: Introductionmentioning
confidence: 99%